Essential oils affect the growth and fatty acid composition of lactobacillus acidophilus - RAM KULKARNI; ASHWIN WADASKAR (International Journal of Pharma and Bio Sciences, 2016)
Lactobacillus acidophilus is an important lactic acid bacterium found in healthy human gut and it also has many food-related applications. Essential oils or their components are used as additives to the dairy products fermented by lactic acid bacteria for imparting the desired flavor. The objective of this study was to assess whether some essential oils affect the growth and fatty acid composition of L. acidophilus. Out of the nine oils tested, cinnamon and clove oils were the inhibitoriest to the growth of L. acidophilus as suggested by broth dilution as well as disc diffusion method. Neem and cinnamon oil caused increase in the proportion of unsaturated and cyclopropane fatty acids in L. acidophilus, respectively. This study signifies the potent application of essential oils for altering the growth and fatty acid composition of lactic acid bacteria which are significant parameters for industrial and health-related usage of these bacteria.